Acute eccentric resistance exercise decreases matrix metalloproteinase activity in obese elderly women. (18th December 2014) - Nascimento, Dahan da Cunha; Navalta, James Wilfred; Durigan, João Luiz Quagliotti; Marqueti, Rita de Cassia; Tibana, Ramires Alsamir; Luiz Franco, Octavio; de Almeida, Jesser Alves; Camarço, Nathalia Ferreira; Neto, Ivo Vieira de Sousa; Prestes, Jonato
Summary: The association of ageing with obesity commits elderly women and has been correlated with multiple degenerative processes, which could be occasioned by an enhancing in levels of matrix metalloproteinase‐2 and metalloproteinase‐9 (MMPs) as well by an cytokine unbalance that included an enhancing on interleukin‐6 (IL‐6). Furthermore, other factors could be also related to degenerative process, as they could be reduced by eccentric resistance exercise (ERE), which seems particularly important to initiate resistance training in obese older adults. In this view, this study aims to determinate the effects of an acute ERE session on serum MMP‐2, MMP‐9 and IL‐6 in elderly obese women. Ten elderly obese women participated in this study and completed a 10 repetitions maximum test (10 RM) utilizing leg extension exercise. Subjects then completed an acute ERE session consisting of seven sets of 10 repetitions at 110% of 10 RM with a rest of 3 min between sets. Blood samples were collected before, immediately after, 3, 24 and 48 h following the ERE session. Zymograms were utilized to measure the MMP‐2 and MMP‐9 enzymes from all individuals. Moreover, IL‐6 concentration was also determinated. After ERE session, MMP‐2 and MMP‐9 decreased, remaining significantly below baseline values after 48 h ( P <0·05). Although not statistically significant, there was a tendency for IL‐6 to decrease 48 h after the ERE when compared with 3 h ( P = 0·06). An acute ERE session decreases MMP‐9, MMP‐2 and IL‐6 in elderly obese women, possibly indicating a transient protection against the low grade inflammation present in this specific population.